Social cognitive career theory: The experiences of Korean college student-athletes on dropping out of male team sports and creating pathways to empowerment - Nam, Benjamin H.; Marshall, Racheal C. (Frontiers in Psychology, 2022)
The South Korean elite sport system is facing a wide range of problems that account for the high dropout rate among college student-athletes. However, research on dropout rates of student-athletes is so far been limited, which amplifies the actual voices of this group, their dropout experiences, and their challenges, while they were in the career transition process. Therefore, this study used a critical phenomenological approach as a primary methodological lens to gather information on 15 formal Korean male college student-athletes on dropping out of team sports, exploring their life challenges during their career transitions out of the sport. The result showed two main thematic categories with sub-themes, which include (1) factors affecting burning out and terminating athletic careers: (a) injury and failure of rehabilitation and (b) bullying and abandonment; and (2) factors hindering post-retirement career advancement: (a) prejudice and exclusion and (b) absence of mentors and counselors. This study used Social Cognitive Career Theory to explore the participants' progression through specific interventions that engage and empower. Overall, the current study calls upon researchers, counselors, and administrators to continue exploring advocacy efforts with this population to alter policy and practice.